Pencegahan Bullying melalui Media Film Education untuk Anak Sekolah SMAN 16 Palembang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Bullying is one of the problems that is rampant in the teenage environment, but it is also possible for it to occur among children. This action can have a long-term negative impact on the mental and emotional development of the victim. Therefore, prevention efforts are needed early on, one of which is through education for the younger generation. Educational films are present as one of the effective media in conveying moral and social messages in an interesting and easy-to-understand way. This study aims to determine whether educational films can make the younger generation aware of the negative impacts of bullying, with SMAN 16 Palembang as the research location. The method used is descriptive qualitative to describe real facts through observation and interviews. The results of the study showed that educational films were able to increase students' awareness of the dangers of bullying and encourage them to be more empathetic and dare to reject bullying in the school environment.